Without Power Comes Great Irresponsibility. Conservative Euroscepticism from Opposition to Brexit (Politeja, 2025)
In this article, we ask how Conservative Euroscepticism was able to transform over the years from a more-or-less reasonable critique of the terms of the Maastricht Treaty to a trenchant opposition to British association with the EU. We argue that policy radicalism is accelerated by a lack of power over policy outcomes, such that political claims (assumptions, policies) cannot be implemented and thus cannot be tested against the harsh light of reality. We argue that stints in opposition, in coalition, and in a state of severe internal division can all lessen the responsibilities of governing and thus remove the onus on political actors to own – and be held accountable for – their policies. This is reinforced by high levels of external interdependence, the instrumental use of policy pronouncements, and hand-tying strategies by governments, all of which diminish any expectation that policies will need to be delivered. Empirically we demonstrate our argument by charting the evolution of Conservative Euroscepticism from the Maastricht Treaty in 1993 to the present day, drawing on a number of elite interviews with current and former Conservative politicians.